Autophagy and inflammatory bowel disease: Association between variants of the autophagy-related IRGM gene and susceptibility to Crohn's disease. Issue 9 (September 2015) - Rufini, Sara; Ciccacci, Cinzia; Di Fusco, Davide; Ruffa, Alessandra; Pallone, Francesco; Novelli, Giuseppe; Biancone, Livia; Borgiani, Paola
Abstract Background Crohn's disease and ulcerative colitis are inflammatory bowel diseases involving a genetically determined inappropriate mucosal immune response towards luminal antigens, including resident bacterial flora. Recent studies identified susceptibility genes involved in autophagy. Aims We analyzed known autophagic loci (IRGM, ULK1 and AMBRA1) previously described as associated with inflammatory bowel diseases or with other autoimmune and/or inflammatory disorders in a sample of Italian inflammatory bowel diseases patients in order to confirm their possible involvement and relative contribution in the disease. Methods We performed a case–control association study, a sub-phenotype correlation and a haplotype analysis. The analysis included 263 Crohn's disease, 206 ulcerative colitis patients and 245 matched healthy controls. Five polymorphisms were genotyped by allelic discrimination assays. Results IRGM was the most strongly associated with Crohn's disease susceptibility [rs13361189: P = 0.011, OR = 1.66 [95% CI: (1.12–2.45)]; rs4958847: P = 0.05, OR = 1.43 [95% CI: (1–2.03)]. The SNP rs13361189 was also found to increase the risk of Crohn's disease clinical sub-phenotype (fibrostricturing behaviour, ileal disease, perianal disease, intestinal resection). These findings suggest that IRGM variants may modulate clinical characteristics of Crohn's disease. Conclusions Our study confirms IRGM rs13361189 and rs4958847 polymorphisms to be important for Crohn's disease susceptibility and phenotype modulation, in accordance with previous findings.